Fetal Outcome in Deliveries with Meconium Stained Liquor - Khatun, Mst Hosna Ara; Arzu, Jahanara; Haque, Emdadul; Kamal, MA; Al Mamun, Mohammad Abdullah; Khan, Mohammad Faizul Haque; Hoque, Md Mahbubul (Bangladesh Journal of Child Health, 2010)
Introduction: Meconium staining amniotic fluid is associated with lots of adverse outcome and has long been considered to be a bad predictor of fetal outcome. Objective: This prospective observational study was undertaken to find out immediate fetal outcome in meconium stained liquor. Materials and Methods: This study was conducted in Obstetrics and Gynecology department of Dhaka National Medical Collage Hospital from July to December 2008. The pregnant women with yellow, brown and thinly stained amniotic fluid in labour with gestational age 37 completed weeks were enrolled in the study. Their babies were taken as case and followed upto 7 days after delivery in National Medical Collage Hospital and in Dhaka Shishu Hospital after admission when required. Babies born without meconium stained liquor were taken as a control. Results: Total 80 cases were enrolled in the study as case and 80 cases were enrolled as control. Mean gestational age was 39.3±1.5 weeks in cases and 38.5±1.3 weeks in control. There was 13.8% pregnancy induced hypertension in case group and 3.8% in control group. Pre-eclampsia were present 10% in case group and 1.1% in control group (p<0.05). Caesarean deliveries were high (75%) in cases and it was much higher with thick meconium (75%) as compared to the thin meconium (25%, p<0.001). Apgar scores in first minute and fifth minute were also low in cases. Birth asphyxia was more in cases (20%). Meconium Aspiration syndrome (25%) and Convulsion (3.8%) were developed only in cases. Admission in neonatal ward was more (22.5%) in cases (p<0.05) as compared to control. Neonatal mortality was high (3.8%) in cases than control (1.3%). Conclusion: Meconium stained amniotic fluid were associated with higher rate of caesarian delivery, increased need for neonatal resuscitation, increased rate of birth asphyxia with hypoxic ischemic encephalopathy, meconium aspiration syndrome, hospital admission and mortality. Key words: Meconium stained liquor; foetal outcome. DOI: 10.3329/bjch.v33i2.5675 Bangladesh Journal of Child Health 2009; Vol.33(2): 41-45